Curcumin-driven reprogramming of the gut microbiota and metabolome ameliorates motor deficits and neuroinflammation in a mouse model of Parkinson’s disease - Cui, Can; Han, Yingying; Li, Hongxia; Yu, Hongxiang; Zhang, Bei; Li, Gang (Frontiers in Cellular and Infection Microbiology, 2022)
Background Parkinson’s disease (PD) is a common neurodegenerative disorder, accompanied by motor deficits as well as gastrointestinal dysfunctions. Recent studies have proved that the disturbance of gut microbiota and metabolism contributes to the pathogenesis of PD; however, the mechanisms underlying these effects have yet to be elucidated. Curcumin (CUR) has been reported to provide neuroprotective effects on neurological disorders and modulate the gut flora in intestinal-related diseases. Therefore, it is of significant interest to investigate whether CUR could exert a protective effect on PD and whether the effect of CUR is dependent on the intestinal flora and subsequent changes in metabolites. Methods In this study, we investigated the neuroprotective effects of CUR on a mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). 16S rRNA sequencing was performed to explore the profile of the gut microbiota among controls, MPTP-treated mice and CUR-treated mice. Then, antibiotic treatment (ABX) and fecal microbiota transplantation (FMT) experiments were conducted to examine the role of intestinal microbes on the protective effects of CUR in PD mice. Furthermore, ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS)-based metabolomics analysis was used to identify the landscape of the CUR-driven serum metabolome. Finally, Pearson’s analysis was conducted to investigate correlations between the gut flora-metabolite axis and CUR-driven neuroprotection in PD. Results Our results showed that CUR intervention effectively improved motor deficits, glial cell activation, and the aggregation of α-synuclein (α-syn) in MPTP-treated mice. 16S rRNA sequencing showed elevated abundances of Muribaculaceae, Lactobacillaceae, Lachnospiraceae and Eggerthellaceae but depleted abundances of Aerococcaceae and Staphylococcaceae in CUR-treated mice when compared with MPTP mice. ABX and FMT experiments further confirmed that the gut microbiota was required for CUR-induced protection in PD mice. Serum metabolomics analysis showed that CUR notably upregulated the levels of tyrosine, methionine, sarcosine and creatine. Importantly, strong correlations were identified among crucial taxa (Aerococcaceae, Staphylococcaceae, Muribaculaceae, Lactobacillaceae, Lachnospiraceae and Eggerthellaceae), pivotal metabolites (tyrosine, methionine, sarcosine and creatine) and the motor function and pathological results of mice. CUR treatment led to a rapid increase in the brain levels of tyrosine and levodopa (dopa) these changes were related to the abundances of Lactobacillaceae and Aerococcaceae. Conclusions CUR exerts a protective effect on the progression of PD by modulating the gut microbiota-metabolite axis. Lactobacillaceae and Aerococcaceae, along with key metabolites such as tyrosine and dopa play a dominant role in CUR-associated neuroprotection in PD mice. Our findings offer unique insights into the pathogenesis and potential treatment of PD.